2013
DOI: 10.1038/npp.2013.109
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Orexin-1 and CRF-1 Antagonism on Stress Circuits: a fMRI Study in the Rat with the Pharmacological Stressor Yohimbine

Abstract: Translational approaches to study the neural substrates of stress and assess the mechanistic efficacy of novel anti-anxiety agents necessitate the use of stressors with a similar degree of saliency across species. The alpha-2 adrenoreceptor antagonist yohimbine represents an attractive experimental tool owing to its well-documented stress-inducing properties in humans and laboratory species. We investigated the neural substrates engaged by yohimbine in the rat brain by using functional magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 72 publications
3
29
0
Order By: Relevance
“…Although this compound exhibits selectivity for the OX1R, particularly at lower doses, there have been some reports that the selectivity and/or stability of SB-334867 may be compromised at higher doses or depending on the preparation (Hollander et al, 2012; McElhinny et al, 2012; Merlo Pich and Melotto, 2014; Winrow and Renger, 2014). The compound used in the current study, GSK1059865, is highly selective for OX1R and exhibits high levels of OX1R occupancy (Bonaventure et al, 2015; Gozzi et al, 2011; Gozzi et al, 2013; Merlo Pich and Melotto, 2014; Piccoli et al, 2012). The compound has no influence on sleep/wake, in contrast with the highly selective OX2R antagonist JNJ10397049 (Gozzi et al, 2011; Piccoli et al, 2012) indicating that behavioral effects of OX1R antagonism are not related to sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this compound exhibits selectivity for the OX1R, particularly at lower doses, there have been some reports that the selectivity and/or stability of SB-334867 may be compromised at higher doses or depending on the preparation (Hollander et al, 2012; McElhinny et al, 2012; Merlo Pich and Melotto, 2014; Winrow and Renger, 2014). The compound used in the current study, GSK1059865, is highly selective for OX1R and exhibits high levels of OX1R occupancy (Bonaventure et al, 2015; Gozzi et al, 2011; Gozzi et al, 2013; Merlo Pich and Melotto, 2014; Piccoli et al, 2012). The compound has no influence on sleep/wake, in contrast with the highly selective OX2R antagonist JNJ10397049 (Gozzi et al, 2011; Piccoli et al, 2012) indicating that behavioral effects of OX1R antagonism are not related to sleep.…”
Section: Discussionmentioning
confidence: 99%
“…This compound has slightly higher selectivity for OX1R vs. OX2R than SB-334867 (~79-fold) and displays none of the significant off-target binding shown by SB-334867 (Gotter et al, 2012). This compound has also been shown to decrease cocaine conditioned place preference and compulsive eating (though not homeostatic or hedonic eating), in the absence of any influence on arousal (Gozzi et al, 2013; Merlo Pich and Melotto, 2014; Piccoli et al, 2012). Based on these results, we predicted that highly selective OX1R antagonism would have minimal influences on hedonic alcohol or sucrose consumption, but would strongly impact dependence-based alcohol drinking, which has been shown to exhibit elements of compulsivity (Vendruscolo et al, 2012; Vendruscolo and Roberts, 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, systemic injections of the OxR1 antagonist GSK-1059865 did not alter corticosterone responses to the pharmacological stressor yohimbine in rats (Gozzi et al, 2011, 2013). Further, oral treatment with almorexant had no effect on basal, social interaction, novelty or restraint stress-induced corticosterone release (Steiner et al, 2013b).…”
Section: Recent Progress Implicating the Orexin System In Stress-relamentioning
confidence: 99%
“…Zhou et al [30] found that in the hypothalamus, neither of these receptors influenced CRH expression, while D 2 receptors appeared to curb cocaine-binge elicited transcription of proopiomelancocortin (POMC). However, recently Gozzi et al reported a profound inhibitory activity of D 1 receptor antagonism on the orexin positive stress and arousal pathways [31]. Therefore, these contradictory findings necessitate stressor specific evaluation of the role of D 1 and D 2 receptor families in HPA activation.…”
Section: Introductionmentioning
confidence: 99%